The kernel is in the least core for permutation games - Tamás Solymosi (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
Permutation games are totally balanced transferable utility cooperative games arising from certain sequencing and re-assignment optimization problems. It is known that for permutation games the bargaining set and the core coincide, consequently, the kernel is a subset of the core. We prove that for permutation games the kernel is contained in the least core, even if the latter is a lower dimensional subset of the core. By means of a 5-player permutation game we demonstrate that, in sense of the lexicographic center procedure leading to the nucleolus, this inclusion result can not be strengthened. Our 5-player permutation game is also an example (of minimum size) for a game with a non-convex kernel.
Keywords: C71; 330; permutation game; least core; kernel